Sociodemographic influences on children’s out-of-school time organized activity participation and physical activity in rural communities: A cross-sectional study - Mary J. Von Seggern; Michaela A. Schenkelberg; Ann E. Rogers; Debra K. Kellstedt; Robin High; Gregory J. Welk; Richard R. Rosenkranz; David A. Dzewaltowski (PLoS ONE, 2025)
Out-of-school time (OST) organized group youth activities (e.g., afterschool programs, clubs) can reduce health inequalities by increasing physical activity (PA). However, unlike youth sport, PA is not the primary focus of many organized activities, and little is known about rural children’s non-sport organized activity participation. This study examined sociodemographic characteristics associated with OST non-sport organized activity participation and PA among children living in rural U.S. Midwest communities. During Spring 2019, children (n = 418 3rd–6th graders) attending school in two rural communities completed a PA surveillance instrument as part of Wellscapes, a community randomized trial. Caregivers of a subsample of children (n = 235) consented to pair their child’s survey results with student enrollment records. Mixed models with community as a random effect examined main and interaction effects of grade, sex, and family income on OST non-sport organized activity participation and these sociodemographic characteristics and organized activity participation on OST moderate-to-vigorous PA (MVPA) per weekday and weekend day. Most children (73.2%) participated in an OST non-sport organized activity. Males were less likely to participate than females (OR = 0.38, 95% CI = 0.20–0.73, p = 0.004). Females and 6th graders reported lower OST MVPA on weekdays and weekends than comparison groups (p < 0.001). Males with lower family income accumulated significantly fewer minutes of MVPA on weekdays (meandiff = -4.7 ± 2.0 minutes) and weekends (meandiff = -8.9 ± 3.8 minutes) compared with males with higher family income (p < 0.05). Many rural children participated in OST organized activities regardless of grade and family income. However, there were disparities in organized activity participation and OST PA outcomes based on sociodemographic factors, including grade, sex, and family income. Designing OST organized activity settings to be more accessible and include opportunities for PA may help ensure children can achieve optimal health.